A proposal for a green supply chain strategy - Carola Pinto Taborga; Amaia Lusa; Anna Maria Coves (Journal of Industrial Engineering and Management (JIEM), 2018)
Purpose: The purpose of this paper is to establish a set of steps for helping companies to create a Green Supply Chain Strategy based on the reduction of their carbon footprint. The aim is to put forward a simple guideline that companies can follow and guide them in achieving their carbon emission targets, as well as obtaining attractive supply chain savings. Design/methodology/approach: Based on a literature review and benchmarking this paper proposes a methodology based on three pillars: 1) Corporate Carbon Strategy; 2) Carbon emission roadmap; and 3) Implementation and tracking. Analytic Hierarchy Process (AHP) techniques were used in order to create a green strategy and support the decision-making processes to select the most interesting alternatives for carbon emission reduction and supply chain savings. The supply chain of a metallurgical company is used to illustrate the case study where the proposed methodology is used. The criteria used for the carbon alternatives selection was based on three factors: 1) the supply chain cost of the alternative; 2) carbon emission impact in terms of CO2 tonnes; and 3) marketing effect. Findings: The paper identifies some specific steps for developing a Green Supply Chain Strategy. The case study developed, demonstrates the importance of following a proper methodology based on a set of steps, it also demonstrates that some alternatives focus on improving the supply chain, such as the facilities location, can also improve the key performance indicator related with carbon emission. Originality/value: The study provides guidance for manufacturing companies in implementing their Green Supply Chain Strategy.
Keywords: 650; carbon dioxide emissions; ahp; green supply chain management